Sustainable design: The exploration of physical forms of recycled materials in furniture studies / Nurul 'Ayn Ahmad Sayuti...[et al.] - Ahmad Sayuti, Nurul 'Ayn; Zainal Abidin, Shahriman (Universiti Teknologi MARA, Kedah, 2012)
Environmental issues have become hit issues nowadays, as the critical usage of natural resources can cause damage and destruction to the environment. Designers and manufacturers currently are searching for and finding solutions to overcome this major problem. New technologies were developed to aid manufacturers in developing new materials from discarded forms or waste materials. In order to save costs, some of the materials were used in a continuous cycle or it is been used in reiterate order called recycling or reusing. Wastes can be considered as non - waste when the wastes are transformed into products giving new functions which will help in reducing the environmental issues. The recycling process will help in preserving the environment for the next generation and at the same time benefiting the economy of the country. The aim of the paper is to determine and identify the flow and flexibility of recycled materials in physical forms to enhance their usage in furniture design.